2020
DOI: 10.1002/admi.202000225
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymer‐Based Nerve Guide Conduits to Promote Peripheral Nerve Regeneration

Abstract: Bridging critical‐sized defects in peripheral nerves to achieve functional recovery is a challenge for orthopedic and hand surgeons. Inadequate regeneration of peripheral nerve axons often results in long‐term partial or total sensory and/or motor impairment. Currently, the best treatment available for long‐gap peripheral nerve regeneration is autologous nerve transplantation, while the successful implementation of this approach requires for secondary surgery and donor nerves. The nerve guide conduit (NGC) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 210 publications
2
50
0
Order By: Relevance
“… Bozkurt et al (2008) used the freeze-drying method to prepare highly oriented 3D porcine collagen scaffolds and found excellent regeneration of Schwann cells (SCs) in vitro . Functional NGCs that support nerve cells and stem cells and NGCs loaded with drugs and nerve growth factors (NGF) are areas of interest for the future ( Dan et al, 2018 ; Zhang et al, 2020 ). Collagen type-I matrix scaffolds loaded with SCs were fabricated by Georgiou et al (2013) , and the results showed that these scaffolds could promote the axonal regeneration in 5 mm defect rat sciatic nerve injury models.…”
Section: Natural Polymer-based Conduitsmentioning
confidence: 99%
“… Bozkurt et al (2008) used the freeze-drying method to prepare highly oriented 3D porcine collagen scaffolds and found excellent regeneration of Schwann cells (SCs) in vitro . Functional NGCs that support nerve cells and stem cells and NGCs loaded with drugs and nerve growth factors (NGF) are areas of interest for the future ( Dan et al, 2018 ; Zhang et al, 2020 ). Collagen type-I matrix scaffolds loaded with SCs were fabricated by Georgiou et al (2013) , and the results showed that these scaffolds could promote the axonal regeneration in 5 mm defect rat sciatic nerve injury models.…”
Section: Natural Polymer-based Conduitsmentioning
confidence: 99%
“…Compared with traditional manufacturing methods (e.g., dip coating, electrospinning, molding), 3D printing has the advantages of being highly cost-effective and having high production efficiency. Several reviews on biomaterials for NGCs have been published (Zhang et al, 2020a), so we will focus on the biomaterials used in additive manufacturing of NGCs in this section.…”
Section: Biomaterials For Additive Manufacturing Of Nerve Guidance Comentioning
confidence: 99%
“…The peripheral nervous system is a network of 43 pairs of motor and sensory nerves that connect the brain and spinal cord (central nervous system) to the entire human body. Epidemiological studies have shown that the incidence of peripheral nerve injury can be as high as 3% of all trauma patients (Zhang et al, 2020a). Connective tissue provides mechanical support for nerve fibers and contains blood vessels, which provide nutritional support for nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible synthetic polymers suit most nerve conduits' fundamental requirements because of their adequate mechanical strength, ductility, and physiochemical compatibility, especially electrospun nanofiber scaffolds [8][9][10]. Nanofibers have attracted attention for their application as nerve conduits due to their softness, flexibility, high porosity, high surface area to volume ratio, and nanoscale diameter [11,12]. Research has shown that nanofiber scaffolds support cellular ingrowth due to their ability to mimic the native tissue or organ [13,14].…”
Section: Introductionmentioning
confidence: 99%